1999
DOI: 10.1002/(sici)1097-0347(199901)21:1<43::aid-hed6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland lesions: Diagnosis of malignancy with MRI and flow cytometric DNA analysis and cytology in fine-needle aspiration biopsy

Abstract: Background The purpose of this study was to assess the capability of magnetic resonance imaging (MRI) and cytology and flow cytometric (FCM) deoxyribonucleic acid (DNA) analysis in fine‐needle aspiration biopsy (FNAB)–derived materials for diagnosing malignancy of the parotid lesions and the efficacy of FCM analysis in FNAB. Methods Magnetic resonance imaging findings and FCM results (ploidy and S + G2 + M phases [S + G2M] fraction) and cytology in FNAB‐derived materials in 26 patients with 26 parotid lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…When this definition was applied to our series, sensitivity, specificity, and accuracy were 52%, 80%, and 73%, respectively. Alternatively, they reported an accuracy of 88% from the viewpoint of unsharp margin [11]. Although Bartels et al showed a sensitivity, specificity, and accuracy of 88%, 77%, and 83%, respectively, they did not refer to MRI features in detail by which to discriminate malignant from benign parotid lesions [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this definition was applied to our series, sensitivity, specificity, and accuracy were 52%, 80%, and 73%, respectively. Alternatively, they reported an accuracy of 88% from the viewpoint of unsharp margin [11]. Although Bartels et al showed a sensitivity, specificity, and accuracy of 88%, 77%, and 83%, respectively, they did not refer to MRI features in detail by which to discriminate malignant from benign parotid lesions [8].…”
Section: Discussionmentioning
confidence: 99%
“…A series of reports have demonstrated the superiority of MRI over CT in delineating parotid mass lesions [6,7]. Although several reports describe which characteristics seen on MRI can effectively differentiate between benign and malignant parotid mass lesions [7Á11], only a few have statistically analyzed such capability of MRI [8,10,11].…”
Section: Introductionmentioning
confidence: 98%
“…A vast majority of studies have used FCM to evaluate DNA content in salivary gland tumours, and the samples have been obtained from fresh tumour tissue or paraffin blocks (10–13, 18, 22–34). Takashima et al (13) suggested that a combination of magnetic resonance, cytology and FCM is optimal for diagnosing malignancies of parotid gland, and fine needle aspiration biopsy (FNAB) derived materials can replace the surgical specimens in FCM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, DNA flow cytometric parameters have prognostic value in some salivary gland carcinomas (10–12). However, there are few series published in the literature focusing on ploidy analysis for prediction of tumour aggressiveness, prognosis, and for differentiating benign from malignant salivary gland tumours (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive resection of any tumor, whether the neoplasm is benign or malignant, can cause serious complications such as facial nerve palsy, and surgeons use the more aggressive approach when they perform surgery to treat malignant tumors (1)(2)(3)(4). Furthermore, preoperative aspiration cytology results are not always conclusive because insufficient specimens are sometimes obtained owing to a small sample size or the deep location of the tumor (5)(6)(7). Therefore, preoperative imaging has an important role in surgical planning.…”
mentioning
confidence: 99%